INFLUENCE OF INTELLECTUAL CAPITAL ON ORGANIZATIONAL PERFORMANCE - Hesniati, Hesniati; Erlen, Erlen (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The research objective to evaluate the effect of intellectual capital on organizational performance in Batam City. Intellectual capital components consist of structural capital, social capital, customer capital, human capital, spiritual capital, and technology capital. This study involved 54 directors of the rural bank. The results of this empirical study indicate that there is a significant relationship between structural capital, customer capital, human capital, and technology capital on organizational performance in Batam City. Meanwhile, social capital and spiritual capital show no significant relationship to organizational performance in Batam City. The results of this study provide additional knowledge about the relationship between intellectual capital and organizational performance.